Monitoring the Paraguayan epidemiological dengue surveillance system (2009-2011) using Benford's law (2016)
Introduction: Dengue is the most widespread arbovirus worldwide. In Paraguay, it reappeared in 1988-1989, with one of the largest epidemic outbreaks occurring in 2011. Objective: To evaluate the performance of the dengue epidemiological surveillance system in Paraguay between 2009 and 2011. Materials and methods: We conducted an ecological study with secondary epidemiological surveillance data. We analyzed notified cases of the disease based on the distribution expected by Benford's law. To this end, we used the first and second digits from the global records stratified by region, season, population density, indicators of housing conditions and heads of cattle. Results: The epidemiological surveillance system performed better during non-epidemic periods and in the states with better housing conditions and fewer heads of cattle. Conclusion: Given that a difference in the performance existed, we recommended that the system remains operating at the same high alert level even during periods when fewer cases are expected. The technology used by the method proposed to monitor the notification of cases is easy to transfer to operational staff.